2016
DOI: 10.5588/ijtld.14.0427
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after anti-tuberculosis treatment completion: results of long-term follow-up

Abstract: Individuals who recover from TB are at higher risk of long-term mortality than the general population, and their causes of death are different. Periodical follow-up might be beneficial for individuals to facilitate early diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 0 publications
4
34
0
Order By: Relevance
“…Wang et al and Huaman et al (2017) reported TB type-specific estimates but we opted to use the overall TB estimates as they were more stable and in line with our protocol [41,43]. We excluded from all meta-analyses two studies (Giral et al, and Shuldiner et al) that presented only frequency tables for CVD outcomes [44,45]. We excluded Mathew et al from the meta-analyses as the authors did not present a definition of CVD and their study contained only 4 deaths from CVD among TB patients [36], excluded Oh et al as they did not provide definitions for TB or CVD [17], and excluded the estimate for females from Blondal et al, as its confidence interval was asymmetrical [39].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Wang et al and Huaman et al (2017) reported TB type-specific estimates but we opted to use the overall TB estimates as they were more stable and in line with our protocol [41,43]. We excluded from all meta-analyses two studies (Giral et al, and Shuldiner et al) that presented only frequency tables for CVD outcomes [44,45]. We excluded Mathew et al from the meta-analyses as the authors did not present a definition of CVD and their study contained only 4 deaths from CVD among TB patients [36], excluded Oh et al as they did not provide definitions for TB or CVD [17], and excluded the estimate for females from Blondal et al, as its confidence interval was asymmetrical [39].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…A study in 27660 SA gold miners over 5 years found progressive FEV1 loss with each tuberculosis recurrence 41 . Former tuberculosis patients are at increased risk of death due to pneumonia and septicaemia 42 , and have reduced longevity 43 , despite TB cure. Multiple inflammatory mechanisms contribute to lung destruction in tuberculosis, including local production and activation of matrix metalloproteinases (MMPs) by tumor necrosis factor (TNF) 44 .…”
Section: Host-directed Therapeutics To Accelerate Cure and Prevent Lumentioning
confidence: 99%
“…Several studies have suggested that factors associated with survival in cases of TB are related to the presence of specific comorbidities, including HIV/AIDS and diabetes mellitus [3][4][5][6][7][8][9]; some clinical characteristics, such as drug resistance, default of treatment, extrapulmonary and mixed forms [3,6,10,11]; specific sociodemographic characteristics of patients (age, male gender, schooling, color or race, etc); and lifestyle, such as alcoholism and smoking [4,7,11,12]. In Brazil, few studies of survival analysis after TB treatment were identified in the literature [7,13].…”
Section: Introductionmentioning
confidence: 99%